1983
DOI: 10.3382/ps.0620746
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Constant Ambient Temperature and Ration on the Performance of Sexed Broilers

Abstract: Two trials involving 480 Cobb color-sexed broiler chicks were conducted to determine the effect of various constant ambient temperatures on the performance of broilers. Temperatures in Trial 1 were 18 and 29 C and in Trial 2 were 24 and 35 C. The interacting effect of dietary energy (3.142 or 3.252 kcal ME/g of diet) and protein (16, 19, or 22%) on performance criteria was also examined within each trial. There was no indication of selective consumption of any of the ratios at any temperature. Differences in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…Resultados semelhantes foram observados por CERNIGLIA et al (1983), FARREL e SWAIN (1987) e PERRALT e LEESON (1992), que verificaram ganhos de pesos significativamente reduzidos, quando compararam grupos de aves com alimentação à vontade e restrita, em altas temperaturas.…”
Section: Methodsunclassified
“…Resultados semelhantes foram observados por CERNIGLIA et al (1983), FARREL e SWAIN (1987) e PERRALT e LEESON (1992), que verificaram ganhos de pesos significativamente reduzidos, quando compararam grupos de aves com alimentação à vontade e restrita, em altas temperaturas.…”
Section: Methodsunclassified
“…Exact heat-stress or hot-climate conditions are difficult to simulate in experi-Continuous selection for increased growth rate thus might increase sensitivity of broiler stocks to high temperatures, unless specific criteria for efficient performance under high temperatures are identified and applied in selection programs. Although in most studies (i.e., Kubena et al, 1972;Cerniglia et al, 1983;Howlider and Rose, 1989) the magnitude of the effect of high temperature was not dependent on sex, Osman et al (1989) found that the reduction in weight gain due to high temperatures appeared at a younger age and was larger in males than in females.…”
Section: Introductionmentioning
confidence: 96%
“…However, the mortality for the birds acclimated to 10 to 12 C for 14 days (followed by acclimation to 28 to 30 C for 7 days prior to aflatoxin-dosing) was no different than that for the birds acclimated to 28 to 30 C for 21 days. DISCUSSION Numerous studies have been conducted to determine the effect of environmental temperature on the feed intake and performance of broiler chickens (Huston, 1965;Deaton et al, 1973Deaton et al, , 1978Hurwitz et al, 1980;Cerniglia et al, 1983;Reece and Lott, 1983). In most studies, measurements were made during the growing-finishing phase from 3 or 4 wk until 7 or 8 wk of age after the chicks were started at normal brooding temperatures.…”
Section: Resultsmentioning
confidence: 99%